The two worlds of nineteenth century international relations the bifurcated century - Green, Daniel M. 1961- (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2019)
"This edited volume presents a new, grand and global narrative for international relations (IR) history in the pivotal nineteenth century. Typically considered by IR scholars to be a long century of relative peace after 1815, the contributors offer a re-conceptualization of IR in this century, arguing that it is temporally bifurcated, with very different patterns of behavior in the first and second halves. A mid-century discontinuity - a "pivot period"--Marks the transition phase in Europe and globally when, in the space of a few years, a shift occurred from a comparatively calm, politically disconnected world under loose British free trade hegemony to one of scrambles for territory and keen interest in imperial possessions and conquest. All the book's chapters deal with characterizing patterns of relations in the first half of the century or the second, with two addressing the discontinuity in the middle. In the first half aspects of regional orders are described (in Latin America, East Asia and Europe) alongside crucial developmental processes (missionaries and colonial expansion, the agency of regionally localized actors, of leading elites). In the second half, there is again discussion of regional developments (East Asia, Europe), but now under the onslaught and pressures of the latter half of the century, and spotlighting industrialization's impact and the role of status competition and international law. In presenting this new narrative for the nineteenth century, it becomes clear that an era long considered uninteresting on Eurocentric grounds is in fact crucial and pivotal in global terms. This work will be of particular interest to students and scholars of the history of international relations"